Does Financial Integration Exist in ECOWAS? - Gidigbi, Matthew Oladapo; Akanegbu, Benedict (Journal of Social and Development Sciences, 2017)
Free movement of goods, capital, and persons have been the long-term strategic goals of the Economic Community of West Africa States (ECOWAS) since its establishment. Notwithstanding, financial integration has become more important in deepening political integration in the region than ever. Assessing how far the Regional Economic Community (REC) has achieved her objective of free movement of capital among the member states. Therefore, this study investigated the existence of financial integration in ECOWAS by employing savings-investment equality, popularly known as Feldstein-Horioka Criterion; a panel data for all the 15 member states was fitted into the specified model. The study found that there is the existence of financial integration in the REC, and that language inhibits financial integration and that the coefficient of language dummy stands at -4.8 percent. However, it found that language inhibition of the financial integration in the REC will gradually disappear over time, as the interactive coefficient of language and time stands at -0.12 percent. This study concludes that a level of financial integration is in existence in the REC. Therefore, the REC is prepared for monetary unification assuming that there will be more substantial trade among the member states.